Neddylation, an Emerging Mechanism Regulating Cardiac Development and Function - Li, Jie; Zou, Jianqiu; Littlejohn, Rodney; Liu, Jinbao; Su, Huabo (Frontiers in Physiology, 2020)
Defects in protein quality control have been increasingly recognized as a pathogenic factor to the development of heart failure, a remaining devastating disease lack of efficacious therapies. A family of small protein modifiers, i.e., ubiquitin and ubiquitin-like proteins, play important roles in controlling protein quality by maintaining the stability and functional diversity of the proteome. The neural precursor cell expressed, developmentally downregulated 8 (NEDD8) is a small ubiquitin-like protein discovered 2 decades ago but the biological significance of its modification (neddylation) in the hart has not been appreciated until recently. In this review, we summarize the current knowledge of the biology of neddylation, sum up several mechanisms by which neddylation regulates the function of its downstream targets, discuss the expanding roles for neddylation in cardiac physiology and disease with an emphasis on cardiac protein quality control, and finally outline the challenges linked to the study of neddylation in health and disease.